2017
DOI: 10.1016/j.techfore.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Emerging energy transitions: PV uptake beyond subsidies

Abstract: a b s t r a c tIn the past decade there has been a substantial increase in the uptake of residential solar photovoltaic (PV) systems globally, which is starting to impact upon traditional electricity systems. An emerging energy transition is being driven by actions taken by actors at the grassroots level, and enabled by declining technology costs and new niche business models. However, to date, most work exploring change in energy systems has tended to focus on technological innovation and economic processes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…Such a mass market could be regarded mature when prosuming gradually becomes independent of subsidies. According to this understanding, none of the three countries studied here show fully mature markets, although examples are emerging in some jurisdictions [27]. Support schemes have been significantly reduced in both Germany and the UK; while this has had visible impact on prosuming uptake, reductions in PV costs may still lead households to install PV panels.…”
Section: Is There a Prosumer Pathway?mentioning
confidence: 87%
See 2 more Smart Citations
“…Such a mass market could be regarded mature when prosuming gradually becomes independent of subsidies. According to this understanding, none of the three countries studied here show fully mature markets, although examples are emerging in some jurisdictions [27]. Support schemes have been significantly reduced in both Germany and the UK; while this has had visible impact on prosuming uptake, reductions in PV costs may still lead households to install PV panels.…”
Section: Is There a Prosumer Pathway?mentioning
confidence: 87%
“…Other studies indicate that approaches to market developments from a 'Varieties of Capitalism' perspective can have important implications for the general uptake of renewables and PV [24]. This may be connected to the observation that in some countries public economic incentives have had an important role in stimulating prosumer developments [1,25], while in other countries household PV uptake has occurred with minimal or no public support [26,27]. PV developments have been shown to be relatively disconnected from natural resource endowments [28], but have been connected to economic support, reduction of transaction costs and bureaucratic hurdles, as well as maturing markets [6].…”
Section: Comparing Prosumer Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social cognitive theories have long been used to explore the adoption of renewable energy and sustainable innovation. Various scholars have employed the lenses of sociotechnical transition models (Dijk, Wells, & Kemp, 2016), innovation ecosystems (Tsujimoto, Kajikawa, Tomita, & Matsumoto, 2017), sustainability management (Luederitz et al, 2016), energy cultures (Ford et al, 2017), escalation of commitment (Ross & Staw, 1993), moral norm activation (Schwartz, 1970), valuebelief-norm model (Stern et al, 1999), and moral self-regulation (Bandura, 2007). These approaches have facilitated the examination of the social acceptance of renewable energy and sustainable innovations.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Past literature (Barbarossa & De Pelsmacker, 2016;Foxon & Pearson, 2008;Stigka, Paravantis, & Mihalakakou, 2014) identifies the crucial element of a successful innovation in the natural resources sector: social acceptance. Studies have identified the following factors as key to consumers' eagerness to adopt renewable energy: egoistic economizing values associated with up-front investment, altruistic values associated with concerns for national prosperity, protections of employees, and sunk costs, and ecological values associated with concerns for the environment (Ford et al, 2017;Ross & Staw, 1993;Yan & Spangenberg, 2018). However, academic research has ignored the incompatible influences of different consumer logics on the adoption of these innovations.…”
Section: Introductionmentioning
confidence: 99%